Pengembangan Aplikasi Native Pelaporan Kerusakan Jalan Pada Platform iOS - Alfin Taufiqurrahman; Fajar Pradana; Fitra Abdurrachman Bachtiar (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Road damage is a common thing found on city streets. Not a bit of road damage causes discomfort in driving to cause accidents. Not a few people are anxious about the road conditions. The amount of public desire to be able to report road damage so that roads can be repaired quickly is quite high. Therefore, a facility is needed for the community to be able to easily and quickly convey their concerns regarding road damage. The Laporjalan application offers these conveniences. By using the geotagging feature and taking pictures with an iOS-based smartphone camera. Using the Firebase database as online storage, users can also find out which roads have road damage, from the level of minor damage to severe damage and monitor the progress of damaged road reports that have been sent. The road damage report sent by the user will be used by the relevant agency as additional information for road repairs. Developed with an iterative method, Laporjalan applications can easily adjust its features to user needs. Based on the results of testing with usability testing, obtained a value of 74 for Laporjalan application, where this value falls into the category of acceptability rating with the level is good so that this application can be said according to user needs.